GAMBARAN STATUS GIZI SISWA-SISWI SMP NEGERI 13 PEKANBARU TAHUN 2016 - Yolanda Syahfitri; Yanti Ernalia; Tuti Restuastuti (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTNutrition in the early adolescents is a matter that must be considered. Many impacts that will be experienced by adolescents when malnutrition. Adolescents who are malnutrition will affect reproduction, in adolescent who experience obesity will be at risk of degenerative diseases. The purpose of this study is to describe the nutritional status of SMP Negeri 13 Pekanbaru. This research were 290 students from grade VII and VIII consisting of 100 boys and 190 girls were taken with quota sampling technique. Data were colected by questionnaire filled out by respondents to assess student characteristics data and calculate BMI by measuring weight and height to get nutritionaly measuring weight and height to get nutritional status of students. Nutritional status is divided into malnutrition, underweight, normal, overweight and obesity based on standard anthropometric indicators BMI per age. The result of this study a normal nutritional status is 172 students (59%), followed by the nutritional status of overweight were 66 students (23%), obesity were 29 students (10%), underweight were 19 students (7%) and malnutrition were 4 students (1%)..Keywords :nutritional status, nutrient, early adolescents